2018
DOI: 10.2196/jmir.7766
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Patient Interest in Provider-Based Consumer Health Information Technology: Survey Study

Abstract: BackgroundConsumer health information technology can improve patient engagement in their health care and assist in navigating the complexities of health care delivery. However, the consumer health information technology offerings of health systems are often driven by provider rather than patient perspectives and inadequately address patient needs, thus limiting their adoption by patients. Consideration given to patients as stakeholders in the development of such technologies may improve adoption, efficacy, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
5
13
0
1
Order By: Relevance
“…Our study clearly indicates that patients and caregivers need to be engaged in the process of developing these tools to ensure the technology fits their needs and will be used. This is consistent with previous research, which suggests that patients should be involved in and guide health technology development [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study clearly indicates that patients and caregivers need to be engaged in the process of developing these tools to ensure the technology fits their needs and will be used. This is consistent with previous research, which suggests that patients should be involved in and guide health technology development [26].…”
Section: Discussionsupporting
confidence: 93%
“…There were a variety of features that survivors wanted in an app, with a priority being options to tailor features to individual needs. The ability to allow participants to interact with mobile features is consistent with previous research [26,27]. Providing options for participants to write in content and complete action plans as part of an online intervention has been shown to have better outcomes (including reduced depression, stress) than those where participants just read online content [28].…”
Section: Discussionsupporting
confidence: 59%
“…Survey questions were developed through an iterative process by the Mentor Leadership Council, which includes a multidisciplinary team with expertise in mentorship, career development, and academic leadership. Questions were assessed and piloted by the council for content, clarity, and comprehensiveness related to the program objectives [23]. The survey consisted of questions related to: college and department affiliations; career development and satisfaction; mentoring activities (e.g., participation in the program, frequency and duration of mentoring meetings, satisfaction across multiple mentoring domains); barriers for the mentee and mentor; interest in mentor training opportunities; demographic questions (optional if faculty had concerns about anonymity); and considering leaving MUSC in the next 2 years.…”
Section: Career Development and Faculty Mentoring Surveysmentioning
confidence: 99%
“…Prior studies have shown that portal utilization may be impeded by limited health and electronic literacy among those with lower income level and educational attainment, which has been characterized as the "digital divide." 23,[29][30][31][32] Portal tasks require more health literacy and familiarity with technology than has been asked of patients previously; yet, it is unclear that the health system is addressing this gap in understanding.…”
Section: Resultsmentioning
confidence: 99%